AN ANALYSIS CODE MIXING AND CODE SWITCHING IN TEACHING MUATAN LOCAL â€œ MUNA LANGUAGEâ€ AT SMP MUNA DISTRIC (MUNA FOLKLORE ) - Suhartini, Sri Wulan; La Ode, Nggawu ((JELE) Journal Of English Language and Education, 2022)
This study aims to determine the type of code-switching and code-mixing used by teachers and students in the learning process, especially in the â€œLocal Contentsâ€ subject. This research was conducted using a qualitative descriptive method. The data collection in this study was carried out by observation and interview, then analysis and describing the results. The results show: The type of code that is often used in this local Load class is Inter-Sentential Switching, with a percentage of 54.3% for this type of code-switching, and for code-mixing, which is often used is Alternation of 47.6%. So, the code switch dominates in this class. The teacher uses folklore as a medium for language learning because it is considered to attract students for the effectiveness of the teaching and learning process. Folklore is deemed to cause relaxing and fun reflexes to reduce boredom; folklore is also considered to rebuild a culture that has begun to be forgotten.